THE INFLUENCE OF INCENTIVES AND WORK MATERIALS ON EMPLOYEE PERFORMANCE AT THE COOPERATIVE, SMALL AND MEDIUM ENTERPRISES OFFICE OF SOUTH TANGERANG CITY - Liawati Liawati; Rr. Ayu Metarini (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of incentives and workload on employee performance at the Cooperative, Small, and Medium Enterprises Office of South Tangerang City. Using a quantitative approach, data were collected through questionnaires from 68 employees and analyzed using statistical methods. The findings indicate that incentives have a significant positive effect on employee performance, as fair compensation enhances motivation and productivity. Similarly, workload significantly influences employee performance, where excessive workloads lead to stress and reduced efficiency. The study also confirms that incentives and workload together have a strong impact on performance, highlighting the need for a balanced human resource strategy. Organizations must ensure fair incentives and manageable workloads to maintain high employee performance. These findings contribute to workforce management strategies in the public sector, emphasizing the importance of aligning compensation policies with employee well-being and efficiency.